Ways of Thinking Dan Ways of Understanding Siswa Dalam Menyelesaikan Soal Bilangan Rasional Ditinjau Dari Teori Harel - Saputra, Ahmad Nur Iryanto; Napitupulu, Bettisari; Tandililing, Pitriana; Panjaitan, Agnes Teresa; Sirampun, Elsi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research is a descriptive qualitative research that aims to describe students' Ways of Thinking and Ways of Understanding in solving arithmetic operation problems of rational numbers reviewed from Harel's theory. The subjects of this study were 19 students of class VII B SMP YPPK Santu Paulus Abepura. The determination of the subjects was carried out using a purposive sampling technique where there were special criteria so that the research objectives were achieved. The data collection technique in this study was an individual test conducted twice and time triangulation was conducted to ensure the validity of the data. The results of the study were that there were five characteristics of students' ways of thinking and ways of understanding in solving rational number arithmetic operations, namely thinking wrong and understanding right (SB), thinking wrong and understanding wrong (SS), thinking wrong (inconsistent) and understanding right (consistent), thinking wrong (inconsistent) and understanding wrong (consistent), and changes in characteristics where students experienced an increase or decrease in characteristics.